1970
DOI: 10.3126/jncs.v23i0.2101
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents of the Bark of Vitex negundo L.

Abstract: Abstractp-Hydroxybenzoic acid (1) and β-sitosterol (2) were isolated, and identified from the methanol and hexane extracts of Vitex negundo. The structure of the compounds were established on the basis of spectral analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Known simple phenolic acids, caffeoyl quinic acids, and flavonoids p-hydroxybenzoic acid 1 (Dhakal et al, 2008), p-coumaric acid 2 (Yi et al, 2010), 3-O-caffeoylquinic acid 3 (Tatefuji et al, 1996), chlorogenic acid 4 (Antognoni et al, 2011), 3,4-O-dicaffeoylquinic acid 5 (Tatefuji et al, 1996), 6 4,5-O-dicaffeoylquinic acid (Tatefuji et al, 1996), luteolin 7 (Xu et al, 2009), luteolin 7-O-glucoside 8 (Zhu and Zhang, 2004), vitexin 9 (Krafczyk and Glomb, 2008), orientin 10 ( Krafczyk and Glomb, 2008), quercetin 3-O-glucoside 11 (Jehle et al, 2010), and isorhamnetin 3-O-glucoside 12 (Olszewska and Roj, 2011) were identified by comparing their spectral data with data published in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Known simple phenolic acids, caffeoyl quinic acids, and flavonoids p-hydroxybenzoic acid 1 (Dhakal et al, 2008), p-coumaric acid 2 (Yi et al, 2010), 3-O-caffeoylquinic acid 3 (Tatefuji et al, 1996), chlorogenic acid 4 (Antognoni et al, 2011), 3,4-O-dicaffeoylquinic acid 5 (Tatefuji et al, 1996), 6 4,5-O-dicaffeoylquinic acid (Tatefuji et al, 1996), luteolin 7 (Xu et al, 2009), luteolin 7-O-glucoside 8 (Zhu and Zhang, 2004), vitexin 9 (Krafczyk and Glomb, 2008), orientin 10 ( Krafczyk and Glomb, 2008), quercetin 3-O-glucoside 11 (Jehle et al, 2010), and isorhamnetin 3-O-glucoside 12 (Olszewska and Roj, 2011) were identified by comparing their spectral data with data published in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bis-sigmodiol (1) and isobavachin (2) [28], five known constituents lupiwighteone (3) [29], orientanol A (4) [30], ergosta-4, 6, 8(14), 22-tetraen-3-one (5) [31], lupenyl acetate (6) [32] and phydroxybenzoic acid [33] have been isolated and characterized (Figure 1). Their brief spectral data are given in Section 3.…”
Section: Resultsmentioning
confidence: 99%
“…E. sigmoidea is an erect woody tree that is about 17 feet tall with a thorny stem and hairy leaves. As a result of this investigation, a new prenylflavanone dimer named bis-sigmodiol (1) was isolated and characterized along with six known constituents isobavachin (2) [28], lupiwighteone (3) [29], orientanol A (4) [30], ergosta-4, 6, 8(14),22-tetraen-3-one (5) [31], lupenyl acetate (6) [32], and p-hydroxybenzoic acid [33] (Figure 1). The known constituents obtained have not been reported so far from E. sigmoidea.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of compounds were established on the basis of extensive analysis of 1 H, 13 C, HMBC, and HSQC NMR experiments as well as comparing with literature data [Figures S1–S10 in supplementary data]. In this way, compounds 1 to 5 were identified as drabanemoroside [30], kaempferol 3- O - α -L-rhamnopyranosyl(1→2)- α -L-rhamnopyranoside [31], kaempferol [32], p -hydroxybenzoic acid [33], and p -coumaric acid [34], respectively.…”
Section: Resultsmentioning
confidence: 99%